2021
DOI: 10.1055/a-1386-6155
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Massage to Reduce Blood Loss Before Delivery of the Placenta in Caesarean Section: A Retrospective Cohort Study

Abstract: Background/Objective To estimate the effectiveness of uterine massage UM in reducing blood loss before delivery of placenta in CS. Methods This was a retrospective cohort study of 1393 women who delivered with CS. Patients who underwent UM (671women) were compared with those who underwent controlled cord traction (722 women). According to risk assessment of PPH, 2 groups were both divided to low risk group and high risk group. Outcomes included blood loss amount within 2 h after delivery, incidence of PPH and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…In a retrospective cohort study by Zhang et women who had high risk for PPH compared to controlled cord traction method during CS. 16 Though there was no significant difference in intractable PPH and incidence of PPH but still they concluded that uterine massage contributed to decreased blood loss during CS in high risk patients for PPH.…”
Section: Discussionmentioning
confidence: 96%
“…In a retrospective cohort study by Zhang et women who had high risk for PPH compared to controlled cord traction method during CS. 16 Though there was no significant difference in intractable PPH and incidence of PPH but still they concluded that uterine massage contributed to decreased blood loss during CS in high risk patients for PPH.…”
Section: Discussionmentioning
confidence: 96%
“…Research has shown that multiple cesarean sections may increase the risk of IPH. [12,13] This is because cesarean section can result in uterine scar formation, and the number and repetition of scars may weaken the uterine muscle layer, thereby increasing the risk of postpartum bleeding. Multiple cesarean sections may further diminish the uterine contractile ability, leading to ineffective contractions and inadequate hemostasis, thereby increasing the incidence of IPH.…”
Section: Discussionmentioning
confidence: 99%